RELATIONSHIPS BETWEEN PROFITABILITY AND FIRM VALUE OF MANUFACTURING COMPANIES IN INDONESIA: THE QUANTILE REGRESSION APPROACH - Muchtar, Darmawati; Rizqon Halal Syah Aji (PT. Radja Intercontinental Publishing, 2024)
This study is attempting to examine the relation of variables using quantile regression approach. This study investigates the relationships between profitability and firm value of manufacturing companies in Indonesia by take into consideration of lagged firm performance ROA(-1) and Tobin’s Q(-1). The profitability measured by return on asset (ROA) and Tobin’s Q is as the firm value. The data of this study retrieved from Indonesia Stock Exchange (IDX) with purposive sample of 110 companies was selected for the period of 2010 to 2019. This study used two sets of quantiles regression (QREGs): 1) A set of additive quantiles regression of ROA on ROA(-1) and Tobin’s Q(-1), and 2) A set of interaction QREGs of ROA on ROA(-1), Tobin’s Q(-1) and ROA(-1)*Tobin’s Q(-1). The results find that all independent of each QREGs are jointly significant. This implies that ROA(-1) has positive significant effect on ROA, adjusted for Tobin’s Q(-1), based on each additive QREG( for = 0.1 to 0.9 at 1 percent level. Moreover, the effects of Tobin’s Q(-1) on ROA, adjusted for ROA(-1), in the nine QREGs has positive significant at 5 percent level, in the QREG(0.9). As well as the Tobin’s Q (-1) has positive significant adjusted effect on ROA, in the two QREG(0.3) and QREG(0.8). Lastly, based on the interaction QREG, ROA(-1) and ROA(-1) interact with Tobin’s Q(-1) also are jointly significant, which shows the effect of ROA(-1) is increasing with increasing scores of Tobin’s Q(-1). This indicates that last year profitability and firm value seems to have effect on current year performance.